2018
DOI: 10.1080/08039488.2018.1430168
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of clients in need of intensive team care in Flexible Assertive Community Treatment in Sweden

Abstract: Clients with psychosis who need ACT may benefit from Flexible ACT through improved social functioning. Being involved in meaningful activities and supported by others are key aspects of recovering from mental illness and are enhanced by Flexible ACT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 26 publications
1
18
0
1
Order By: Relevance
“…Data from the FACT board showed that the median duration of a FACT board episode was only 12 days, considerably shorter than results of other studies of FACT conducted in the Netherlands and Sweden; Nugter el al. 5 reported a median of 12•6 weeks, and Svensson et al 7 reported a mean of 6 months. A possible explanation could be a larger caseload in the Danish teams compared with that recommended in the Dutch FACT manual.…”
Section: Comparison With Other Fact Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from the FACT board showed that the median duration of a FACT board episode was only 12 days, considerably shorter than results of other studies of FACT conducted in the Netherlands and Sweden; Nugter el al. 5 reported a median of 12•6 weeks, and Svensson et al 7 reported a mean of 6 months. A possible explanation could be a larger caseload in the Danish teams compared with that recommended in the Dutch FACT manual.…”
Section: Comparison With Other Fact Studiesmentioning
confidence: 99%
“…Contacts are less frequent than in ACT, with most appointments offered at the team office and within usual office hours. 3 Although the FACT model has been taken up in many countries [5][6][7] , there is a lack of good quality studies investigating its effectiveness. [8][9][10] To date, no studies have compared FACT with ACT or CMHT control groups .…”
Section: Research In Context Panelmentioning
confidence: 99%
“…They largely link services and contribute to a clearer and more integrated system. In addition, a Swedish study assumed that FACT teams appear to bridge gaps between services [6]. FACT teams as a binding collaboration between specialist and primary care appear to be of great importance in their role as a bridge.…”
Section: Fact Teams Contribute To Positive Changes In the Service Systemmentioning
confidence: 99%
“…15 :38 at providing integrated care for people with severe mental illness (SMI) [4]. The model was developed in the Netherlands [5], has spread internationally [6][7][8][9][10][11] and has been implemented in the Netherlands [12,13], Norway, Sweden, England [7] and Denmark [8]. The Norwegian health authorities have funded implementation of FACT teams since 2013, resulting in approximately 70 teams being implemented.…”
mentioning
confidence: 99%
“…En oppsummering av fem studier viste at en ikke finner signifikant bedring hos pasienter i FACT når det gjelder symptomreduksjon eller funksjonsnivå, men studiene hadde flere metodiske svakheter som liten styrke i utvalgene, uklare kriterier for mål på symptomer, ulikheter i utvalg som sammenliknes, samt uklarheter rundt hva som er faktiske resultater og hva som er antakelser (Nordén & Norlander, 2014). Nyere forskning som har undersøkt effekten av FACT i Nederland, Sverige og Danmark har vist bedring i psykososial fungering, livskvalitet og etterlevelse av behandling, samt nedgang i udekkede behov, antall innleggelser og lengde på innleggelsene (Nugter et al, 2016;Kortrijk et al, 2019;Svensson, Hansson & Lexen, 2018;Lexen & Svensson, 2016;Nielsen, Hjorthøj, Killaspy & Nordenhoft, 2021). Den norske evalueringsstudien av FACT viste at pasienter som var fulgt opp i to år hadde oppnådd bedre bosituasjon, økt deltakelse i meningsfull aktivitet, bedre praktisk og sosial fungering, mindre symptombelastning og økt livskvalitet (Landheim & Odden, 2020).…”
Section: Bakgrunnunclassified